The tender organs - Janecek, Carolyn Eugenia, author; Dungy, Camille T., advisor; Cooperman, Matthew, advisor; McShane, Katie, committee member (Colorado State University. Libraries, 2023)
The Tender Organs is an ecopoetic coming-of-age narrative that explores embodiment and inheritance. Taking on hybrid forms, these poems reach beyond the binaries of male and female, human and animal, history and present, visibility and invisibility. Each section situates itself in a different time of the speaker's life: grappling with puberty and cultural miscommunication as a dual citizen; grieving one's friend and mentor; investigating the medicalizing, patriarchal gaze of U.S. healthcare; and finally, exploring the possibilities of rapture and relationships outside of the societal binaries.
Keywords: poetry; ecopoetic